Asymptotic Analysis of the Non-Stationary Cross-flow Vortices on a Rotating Disk with Temperature-Dependent Viscosity - Jasmine, HA (GANIT: Journal of Bangladesh Mathematical Society, 2011)
Asymptotic analysis of the non-stationary cross-flow disturbances of Von-kármán rotation disk flow with a temperature dependence viscosity is investigated. The linear eigenrelations are derived for various values of the parameter which controls the temperature dependence of viscosity with more than one critical layer. It has been fund that there is a cut-off value at an angle that lies between 10.3° and 57.4°, so that solution exist only for this range. GANIT J. Bangladesh Math. Soc. (ISSN 1606-3694) 29 (2009) 51-62 DOI: http://dx.doi.org/10.3329/ganit.v29i0.8515